Courageous companions : followership in Doctor Who - Yost, Kimberly (Exploring effective leadership practices through popular culture, 2024)
Followership as a separate concept within leadership studies gained prominence in the 1990s and has evolved over the past few decades into an indispensable component of the discipline. Nevertheless, misunderstandings about followers and their relationship to leaders prevail. Exploring what it takes to be a follower is increasingly important in the current organizational, social, and political landscapes rife with narcissism, a seemingly acceptable leadership characteristic in the twenty-first century. Being a follower to a mercurial leader isn't easy - especially if they are an alien Time Lord who has lived for centuries in various body incarnations. Followers must not be passive, but full partners in the leader/follower relationship to enable them to reach goals and provide the skills and perspectives leaders need for organizational success. Requiring courage, the numerous and varied companions in the TV series Doctor Who provide a compelling and interesting example of followership from which we can learn to become better, more courageous, followers. By leveraging the intersection of popular culture, leadership theory, and followership theory, Courageous Companions offers an accessible new perspective for those who desire to gain a greater understanding of leaders and followers to transform their relationships and organizations. Exploring Effective Leadership Practices through Popular Culture aims to bring examples, theory and methodology of leadership to life by analysing academic concepts through popular culture examples that will appeal to a broad range of readers.